Transcatheter aortic valve in mitral annular calcification (TAV-in-MAC): A new treatment option for mitral valve replacement in patients with severe annular calcification - Weich, Hellmuth; van Wyk, Jacques; Hofmeyr, Lou; Vogts, Carl (SA Heart Journal, 2019)
Severe mitral annular calcification is not an uncommon occurrence in the elderly and up to now, this has often precluded surgical replacement of the mitral valve. Initial attempts at percutaneous placement of transcatheter aortic valves in the calcified mitral annulus, has not been very successful due to obstruction of the left ventricular outflow tract. We describe a surgical approach where the anterior mitral valve leaflet was resected and a balloon expandable transcatheter aortic valve then deployed within the calcified annulus. The benefits of this technique over a fully percutaneous approach is discussed.